THE ROLE OF SCHOOLS IN EDUCATING CHILDREN FOR LEISURE TIME AND IN LEISURE TIME - Daria Jašarević; Benjamin Avdić; Edina Kuduzović; Lidija Kobelja; Matea Andrejaš (Research in Education and Rehabilitation)
Leisure time in contemporary society is increasingly becoming a crucial factor in shaping the personalities of children and youth. Alongside family, schools play a central role in organizing and shaping students' leisure time. The aim of this paper is to examine the role of schools in the pedagogical structuring of students’ leisure time and to explore differences in the perception of leisure time between students in urban and rural schools. The research was conducted on a sample of 140 seventh-grade students from elementary schools in the Tuzla Canton. The study analyzed students' ways of spending leisure time, the involvement and support of schools in organizing leisure time, and the perception of societal support for students' leisure activities. The results of the research indicate that students most frequently spend their leisure time in activities without significant pedagogical influence. Most students occasionally participate in school clubs, with significant differences observed between urban and rural schools in the type and number of activities available. Teachers and parents are the primary sources of support in organizing leisure time, while the broader community offers limited support. The findings suggest that schools play an important role in the organization of leisure time but that there are significant disparities in the activities available to students in different environments. Although activities such as sports and cultural clubs remain popular, students are increasingly gravitating towarddigital content, which may reduce the pedagogical value of leisure time. Schools should continue to develop and adapt leisure activities to meet students’ needs, with greater involvement from the broader community and support in fostering healthy and constructive patterns of leisure time usage.